Functional and Morphological Reproductive Aspects in Male Rats Exposed to Di-n-Butyl Phthalate (DBP) in Utero and During Lactation - Scarano, Wellerson R. [UNESP]; Toledo, Fabiola C.; Guerra, Marina T.; Pinheiro, Patricia F. F.; Domeniconi, Raquel F.; Felisbino, Sergio L.; Campos, Silvana G. P. [UNESP]; Taboga, Sebastiao R. [UNESP]; Kempinas, Wilma G. (Taylor & Francis Inc, 2010)
The potential adverse reproductive effects, with emphasis on the epididymis, of in utero and lactational exposure to 100 mg/kg/d di-n-butyl phthalate (DBP) in adult male rat offspring were investigated. The fetal testis histopathology was also determined. The selected endpoints included reproductive organ weights, sperm motility and morphology, sperm epididymal transit time, sperm quantity in the testis and epididymis, hormonal status, fetal testis and epididymal histopathology and stereology, and androgen receptor (AR), aquaporin 9 (AQP9), and Ki-67 immunoreactivities. Pregnant females were divided into two groups: control (C) and treated (T). The treated females received DBP (100 mg/kg/d, by gavage) from gestation day (GD) 12 to postnatal day (PND) 21, while control dams received the vehicle. Some pregnant dams were killed by decapitation on GD20, and testes from male fetuses were collected for histopathogy. Male rats from other dams were killed at PND 90. Fetal testes from treated group showed Leydig-cell clusters, presence of multinucleated germinative cells, and increase of the interstitial component. Testosterone levels and reproductive organ weights were similar between the treated and control adult groups. DBP treatment did not markedly affect relative proportions of epithelial, stromal, or luminal compartments in the epididymis; sperm counts in the testis and epididymis; sperm transit time; or sperm morphology and motility in adult rats. The AR and AQP9 immunoreactivities and proliferation index were similar for the two groups. These results showed that fetal testes were affected by DBP as evidenced by testicular histopathologic alterations, but reproductive parameters and epididymal structure/function were not significantly altered in the adult animals exposed to 100 mg/kg DBP in utero and during lactation.